A Study Of Verbal Expressions Denoting Politeness Strategies Used In Beauty Contests In English Versus Vietnamese - Hà Thị Kiều Phượng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis is designed to study theverbal expressions denoting politeness strategies used in Interviewing- Responding in Beauty contestsin English and Vietnamese. This study is based on the theory of Notion of Face raised by Brown and Levinson (1987) as well as Politeness Principles of Leech (1983) in association with Social-Norm on Politeness. The basic view of this paper is that there are differences between English and Vietnameseusing politeness strategies in Interviewing- Responding in the final round of Beauty contests and that these differences originate from different cultures. Using the contrastive analysis of 120 samples from English interviewing,120 samples from Vietnamese interviewing, 120 samples from English responding and 120 samples from Vietnamese responding, we could find that native English and Vietnamese speakers use four main politeness strategies ranging along a scale of increasing level of indirectness, namely Direct Strategy Category (DC), Conventionally Indirect Strategy Category (CI), Non-Conventionally Indirect Strategy (NI) and Discourse Indirectness Strategy (DI). By describing and comparing linguistic features in these different strategies, the research discovers the similarities and differences between them in the two languages. These differences can cause many difficulties in communication for English learners of Vietnamese and Vietnamese learners of English as a foreign language. We hope that the findings of this study could provide a deeper insight into the Interviewing and Respondingin differentcultures as well as help the interlocutors find an effective way in dealing with cross-culture communication. We also expect that this study could be a useful reference for other pragmatists.